THE IMPLEMETATION OF SEMANTIC MAP TO ENHANCE THE STUDENTS WRITING ABILITY OF PASSIVE VOICE TO THE ELEVENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL 9 PALEMBANG - Marleni, Marleni (English Community Journal, 2017)
The main problem of this study was Is it effective to teach Passive Voice by using semantic map to the eleventh grade students of state Senior High School 9 Palembang. The method of this study was preexperimental method with one group pre-test and post-test design. The data were collected through two kinds of test, pretest and posttest. The data were analyzed by using the matched t-test. Based on the result of the data analysis, the students average score in the pre-test was 51,63, and the average score in the post-test was 63,68. The t-table of 5 % significance level was 1.684. It could be concluded the value of tobtained (7,21) was higher than the value of t-table (1.684). It means that Ho was rejected, and consequently Ha was accepted.